Identification and nucleotide sequences of two similar tandem direct repeats in Epstein-Barr virus DNA. - Dambaugh, T R (1982)
Epstein-Barr virus DNA is known to have partially homologous segments, designated DL and DR, near the left and right ends of the long unique region (Raab-Traub et al., Cell 22:257-267, 1980). DL and DR are each partially composed of tandem direct repeat sequences. DL contains 11 to 14 repeats of a 124-base-pair sequence designated IR2. DR contains approximately 30 direct repeats of a 103-base-pair sequence designated IR4. The DL and DR sequences have colinear partial homology for approximately 2.4 and 1.5 kilobase pairs to the right of IR2 and IR4, respectively. IR2 and IR4 are similar sequences and evolved in part from a common ancestor. Both sequences are 84% guanine and cytosine and have limited homology to Epstein-Barr virus IR1 and to the herpes simplex virus type 1 inverted terminal repeat "a" sequence. IR2 encodes part of an abundant 2.5-kilobase persistent early EBV RNA expressed in productively infected cells, but does not encode part of the 3-kilobase Epstein-Barr virus RNA which is transcribed from the adjacent IR1-U2 region of the Epstein-Barr virus genome in latently infected cells.